The fate of nitrogen during agricultural intensification in East Africa: nitrogen budgets in contrasting agroecosystems - Tully, Katherine L.; Hickman, J.E.; Russo, T.A.; Neill, C.; Matata, P.; Nyadzi, G.; Mutuo, P.; Palm, C.A. (American Geophysical Union, 2023)
The intensification of agricultural systems in sub-Saharan Africa (SSA) is necessary to reduce poverty and improve food security, but increased nutrient applications in smallholder systems could have negative consequences for water quality, greenhouse gas emissions, and air quality. We tracked nitrogen (N) inputs and measured maize (Zea mays) biomass, grain yields, N leaching, and nitric oxide (NO) and nitrous oxide fluxes from a clayey soil in Yala, Kenya and a sandy soil in Tumbi, Tanzania, with application rates of 0, 50, 75, 100, 150, and 200 kg N ha−1 yr−1 over two cropping seasons. Maize yields were 4.5 times higher in Yala than Tumbi, but yields plateaued at both sites with fertilizer applications at or above 100 kg N ha−1 yr−1. Partial N budgets in Yala were typically negative, meaning more N was exported in maize biomass plus grain or lost from the system than was added in fertilizer. In Tumbi, N budgets were negative at lower fertilizer levels but positive at higher fertilizer levels. At both sites most (96%) of the N was lost through maize biomass/grain removal and N leaching. Fertilizer additions at or less than 50 kg N ha−1 yr−1 on these two contrasting sites resulted in minor gaseous N losses, and fertilizer additions less than 200 kg N ha−1 yr−1 caused relatively little change to N leaching losses. This indicates that the modest increases in fertilizer use required to improve maize yields will not greatly increase cropland N losses.